Satisfaction and continued intention of digital textbook of language assessment and evaluation: Expectation-Confirmation Model (ECM) perspective - Zulkifli Nur Aisyah (Proceder: Applied Linguistics, Literature, and Language Education, 2025)
This study aimed to measure students’ satisfaction and intention to continue utilizing the Expectation-Confirmation Model (ECM) for digital purposes. The specific objective of this study was to examine the relationship between confirmation and satisfaction using digital books. The total number of participants was 85 students from the English Education Department. The findings indicate that confirmation is favorably connected to both post-adoption expectation variables and students’ satisfaction with digital books. Finally, digital text content needs to be produced to offer clear and relevant learning material, as well as to provide cohesive and successfully structured what is learned.